KEADAAN LINGKUNGAN FISIK RUMAH PENDERITA TUBERKULOSIS PARU DI KECAMATAN TANGGULANGIN KABUPATEN SIDOARJO - Sudarso Sudarso (Purifikasi, 2010)
Most of infectious diseases are influenced by physical, biological, chemical, economical, and cultural environmental factors. One of infectious diseases in Indonesia, which has not been able to be eliminated, is tuberculosis. The incidence rate of tuberculosis in Indonesia is 583.000 cases/year. This disease can kill 140.000 patients nationally per year, and has become the second death cause after heart disease. The sanitation condition of lung tuberculosis patient houses was improper, particularly the humidity, air temperature, ventilation, and dweller density. The number of tuberculocis cases in Tanggulangin District was 50, the highest when compared to those of other Districts. This situation revealed that the sanitation condition of the tuberculosis patient houses in this District did not meet the health criteria. Therefore, this research was focused on the influence of physical condition of houses to lung tuberculosis incidence in Tanggulangin District, Sidoarjo. This research was designed it use observational case-control approach. Data analysis was done using Chi-square, Two-sample, and Mann Whitney Tests. The Ratio Odds values concluded that the dweller density, natural lighting condition, ventilation, and humidity influenced the tuberculosis incidence in the study area. Temperature theoretically influenced the pathogen’s growth. However, this research showed that temperature did not give effect on tuberculocis incidence in the study area.